Determination of dielectric properties of 5CB nematic liquid crystal doped with new chiral calamitic compounds - Canli, N. Yilmaz; Ozukanar, D.; Vardar, D.; Kavak, P.; Bozkurt, A. Asikoglu; Ocak, H.; Eran, B. Bilgin (SPRINGER, 2023)
Nematic liquid crystals are widely used in display technologies. In this research area, nematic liquid crystals (LCs) are doped with different LC materials to obtain modified LC properties which response desired physical properties in display technology. Here, the dielectric properties of 5CB (4-cyano-4 '-pentylbiphenyl) nematic liquid crystal which was doped with two pyridine-based chiral calamitic compounds with different number of aromatic rings as well as a branched chiral side chain, which is (S)-3,7-dimethyloctyloxy were investigated. The new composites of non-mesomorphic 4-((S)-3,7-dimethyloctyloxy)phenyl 6-chloronicotinate (Cr) and (4-[4-((S)-3,7-dimethyloctyloxy) phenoxycarbonyl] phenyl 6-chloronicotinate (LC) which exhibits enantiotropic SmA mesophase were prepared using 2 wt% and 5 wt% with respect to the 5CB. The effects of doping with 2 wt% and 5 wt% of new chiral calamitics on dielectric properties of 5CB have been investigated at room temperature. The dielectric parameters (e ', e '', Delta e (dielectric strength), f(r) (relaxation frequency) were determined by dielectric spectroscopy method. The real part of the dielectric constants increases as 2%, 5% LC are added to 5CB, and decreases as 2%, 5% Cr are added to 5CB. It was observed that the diameter of the Cole-Cole graphs, Delta e and e(max)'' data increased with the addition of LC to 5CB, and the two liquid crystal mixture improved the dielectric properties of the material. It has been also determined that adding LC to 5CB, increases the concentration dependent dielectric strength.
Keywords: COMPLEXES; DEVICES; Engineering; Materials Science; Physics